Anode for electrochemical energy storage device
By using silicon-carbon composite materials, graphite, carbon nanotubes and polymer adhesives in the anode of the electrochemical energy storage device, the problems of insufficient charging time, cycle stability and life in the prior art are solved, and rapid Charging and long lifespan effects.
Patent Information
- Application Number
- CN202380047252.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing electrochemical energy storage devices have shortcomings in charging time, cycle stability and life, and it is difficult to meet the needs of fast charging and long life.
An anode containing silicon-carbon composite materials, graphite, carbon nanotubes and polymer binders is used to improve the conductivity and mechanical stability of the anode by optimizing the proportion and structure of these materials.
It significantly improves the charging time of the electrochemical energy storage device, improves cycle stability and life, enhances electrochemical properties, and meets the needs of fast charging and long life.
Smart Images

Figure CN119487650A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an anode for an electrochemical energy storage device, such as a secondary battery. In particular, the present invention relates to an anode for an electrochemical storage device, the anode comprising a silicon-carbon composite material. The present invention further relates to an electrochemical energy storage device comprising such an anode. Background Art
[0002] Electrochemical energy storage devices are well known in the art. In particular, in view of the progress in the electrification of vehicles, electrochemical energy storage devices are becoming increasingly important. For this, and in particular in order to gain better acceptance on the market, the charging time becomes more important.
[0003] Due to the rapidly increasing importance of electrochemical energy storage devices, in particular Li-ion batteries, there is a constant need for further developments and improvements in the field of forming such devices.
[0004] Based on the above, an object of the present invention is to at least partially overcome at least one disadvantage of the prior art. In particular, an object of the present invention is to provide an electrochemical energy storage device that exhibits a fast charging time. Another object of the present invention is to provide an electrochemical energy storage device that exhibits good cycle stability and long life.
[0005] The object is solved by an anode for an electrochemical energy storage device having the features of claim 1. The object is also solved by an electrochemical energy storage device having the features of claim 11. Preferred embodiments of the invention are described in the dependent claims and in the following description, which, unless expressly excluded, each may represent an aspect of the invention alone or in combination. When a feature is shown in combination with another feature, this is only to simplify the description of the invention and is by no means intended to imply that the feature could not be another feature of the invention without the other feature. Summary of the invention
[0006] An anode for an electrochemical energy storage device is described, the anode comprising at least
[0007] - a silicon-carbon composite material in an amount of ≥ 45 wt.-% to ≤ 90 wt.-%, relative to the anode;
[0008] - graphite in an amount of ≥ 5 wt.-% to ≤ 47 wt.-%, relative to the anode;
[0009] - carbon nanotubes in an amount of >0 wt.-% to <1 wt.-% relative to the anode; and
[0010] - a binder, in particular a polymeric binder, in particular in an amount of 3 to 8 wt.-%, relative to the anode.
[0011] The abovementioned components may amount to up to 100 wt.-%, relative to the anode.
[0012] Such anodes show significant improvements when used in electrochemical energy storage devices, especially lithium batteries, as shown in more detail below.
[0013] All the previously described materials, such as in particular silicon-carbon composites, graphite, carbon black, carbon nanotubes, present in a binder, can form the anode and be provided on a metal foil in order to form the final anode electrode for an electrochemical storage device.
[0014] The described anode contains a silicon-carbon composite in an amount of ≥45 wt.-% to ≤90 wt.-% relative to the anode and preferably a silicon content of ≥18 to ≤45 wt.-%. Such a silicon-carbon composite may also be referred to as a silicon-carbon composite mixture.
[0015] The term carbon refers to a material or substance consisting of or at least comprising carbon. To this end, carbon materials can include high purity, amorphous and crystalline materials. Carbon can be activated carbon, pyrolyzed dry polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, activated dry polymer gel, activated polymer cryogel, activated polymer xerogel, activated polymer aerogel or a combination thereof. In another embodiment, carbon can be produced by pyrolysis of coconut shells or other organic wastes. To this end, polymers are molecules comprising two or more repeating structural units. Porous carbon provides advantages of being generally easy to produce, generally having low impurities and large pore volume. Therefore, porous carbon exhibits good electrical conductivity and high mechanical and chemical stability. In one embodiment, the carbon material has a high micropore volume ratio as described in more detail below.
[0016] In another embodiment, the carbon is a hard carbon material, graphite carbon, or an oxide containing compound. For example, the oxide containing compound is silicon oxide (SiO2). Alternatively, the oxide containing compound is titanium oxide (TiO2), tin oxide (SnO2), or other oxides. The hard carbon material is a non-graphitizable carbon material. Hard carbon provides the advantage that it remains amorphous at elevated temperatures (typically >1500°C), while "soft" carbon crystallizes and becomes graphite.
[0017] In one embodiment, the carbon can be a modified hard carbon. The modified hard carbon is a composite material comprising both carbon (particularly hard carbon) and a lithium alloy material. The lithium alloy material can be silicon, tin, germanium, nickel, aluminum, manganese, aluminum oxide (A12O3), titanium, titanium oxide, sulfur, molybdenum, arsenic, gallium, phosphorus, selenium, antimony, bismuth, tellurium or indium or any other metal or metalloid capable of absorbing lithium.
[0018] The silicon portion may be pure silicon or a material composition containing silicon. For example, the silicon portion may be at least one alloy. The alloy may be a silicon-titanium alloy (Si-Ti), a silicon-iron alloy (Si-Fe), a silicon-nickel alloy (Si-Ni). In another embodiment, the silicon portion may be composed of a P dopant, an As dopant, or an N dopant. The P dopant is typically a phosphorus dopant, the As dopant is typically an arsenic dopant, and the N dopant is typically a nitrogen dopant.
[0019] The presence of silicon in the silicon carbide composite material can be advantageous because, in general, silicon has a significantly higher energy density than, for example, graphite. For example, the energy density of silicon exceeds energy density of graphite by a factor of ten.
[0020] It may be further provided that, in addition to the described (first) silicon-carbon composite material, the anode also comprises another silicon-carbon composite material different from the first silicon-carbon composite material. In a further embodiment, the anode may comprise another carbon and / or another binder, as described below. At least one other carbon and / or at least one binder may be dissolved in an aqueous medium. The other carbon may be a hard carbon material or graphite carbon or a compound comprising an oxide.
[0021] The anode according to the present invention further comprises graphite. Graphite is generally known as an anode material for lithium batteries or lithium ion batteries, respectively. Generally, graphite is an excellent anode material and has been known for a long time for lithium ion batteries, with the advantage of its relatively low cost, abundance, high energy density, power density, and an incomparable balance of very long cycle life. However, in electrochemical energy storage devices of the prior art, graphite is mainly present in the composition as a material that is dominant in quantity. Compared with this arrangement and according to the present invention, graphite is present in the anode in a relatively small amount, i.e., an amount of ≥5wt.-% to ≤47wt.-% relative to the anode.
[0022] Surprisingly it has been found that exchanging the bulk of graphite by means of a carbon-silicon composite material allows even improved properties compared to pure graphite or bulk graphite.
[0023] Furthermore, the described anodes contain carbon nanotubes in an amount of >0 wt.-% to <1 wt.-% relative to the anode. Surprisingly, it has been found that the addition of carbon nanotubes can even further enhance the electrochemical properties of the anode and thus the electrochemical energy storage device. In particular, the charging time can be further improved.
[0024] Carbon nanotubes can be described as having a diameter in the range of 2 to 5 nanometers, for example, an allotrope of carbon with a hollow structure and a high aspect ratio (length / diameter ratio) of about 200 to 5000. Carbon nanotubes such as single-walled carbon nanotubes (SW-CNTs) can exhibit significant electrical conductivity. SW-CNTs can be grown on silicon substrates using a chemical vapor deposition (CVD) method and represent an electrically uniform array of single-walled carbon nanotubes. In some embodiments, the single-walled carbon nanotubes are provided as a suspension in water together with some stabilizing polymers.
[0025] As regards suspensions, these allow particularly easy processing, since a suspension of carbon nanotubes in water is a very homogeneous solution.
[0026] It has been shown that the described advantages can be achieved particularly effectively in the case where the carbon nanotubes comprise single-walled carbon nanotubes. However, the present invention also does not exclude that the carbon nanotubes are multi-walled carbon nanotubes.
[0027] Furthermore, a binder is present in the anode in an amount of, for example, 2.5 wt.-%, such as 3 wt.-% to 8 wt.-%, relative to the anode. A binder is a binding agent or a binding material in a manner known per se. Thus, a binder refers to a material that can hold together the individual components of a substance, in particular particles, such as carbon and silicon-carbon composites. The binder is generally arranged so that when the particles are combined with the respective binder, a cohesive mass is formed, which can be further shaped into new forms.
[0028] The binder can be configured to bind all compounds present in the anode, such as, in particular, the particularly porous carbon and silicon content (silicon content), graphite and carbon nanotubes of the first silicon-carbon composite material. In another embodiment, the binder is adapted to bind the additional material to at least one of the corresponding silicon-carbon composite materials. Thus, the binder is typically arranged to hold together the components of the silicon-carbon composite mixture and, optionally, the additional carbon material of the electrode that may form the anode.
[0029] The anode may contain at least one further binder. This leads to the following advantages: the carbon increases the conductivity of the electrode and thus provides improved conductivity. The at least one further binder also supports mechanical stability.
[0030] The anode may comprise at least two binders, wherein a first binder is arranged to bind a particularly porous carbon and silicon-carbon portion of a first silicon-carbon composite material and a particularly porous carbon and silicon portion of at least one additional silicon-carbon composite material, and wherein at least one additional binder is arranged to bind the first silicon-carbon composite material to at least one additional silicon-carbon composite material.
[0031] Optionally, the silicon-carbon composite material comprises at least one further binder adapted to bind the first material component and the at least one further material component together.
[0032] For example, the binder is a styrene-butadiene rubber / carboxymethyl cellulose (SBR / CMC) mixture, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA). In an alternative embodiment, the binder is formed as a fluoropolymer, such as polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), polyethylene tetrafluoroethylene (ETFE), polyvinyl fluoride (PVF), polyethylene trifluorochloroethylene (ECTFE), (polyvinylidene fluoride (PCDF), (polytrifluorochloroethylene (PCTFE), trifluoroethanol or a combination of at least one of these materials and at least one other material. In a further embodiment, the binder is a copolymer of polyimide or polyacrylic acid and styrene-butadiene. However, it is particularly preferred that the binder is a styrene-butadiene rubber / carboxymethyl cellulose (SBR / CMC) mixture, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA).
[0033] Typically, the adhesive can be used in either an organic or water-based solution.
[0034] The described anodes exhibit the advantage of excellent charging times, which allow electrochemical energy storage devices to be charged from a very low state of charge to a very high state of charge in a very short time. This significantly improves market acceptance.
[0035] In particular, considering secondary batteries used in vehicles, charging time is an important factor that can improve the acceptance of electric vehicles. Therefore, improving charging time in particular is an important characteristic of secondary batteries for vehicles (such as cars). However, it should of course be noted that the anodes described herein and therefore the electrochemical energy storage devices are not limited to use in vehicles.
[0036] In addition to the above and the charging time, other characteristics of the anode are not deteriorated, such as long life, high cycle stability and damage resistance.
[0037] The silicon-carbon composite material mixture can be formed so that the silicon-carbon composite material mixture has a range from 0.09 g / cm 3 Up to 1.5g / cm 3 , or from 1.1g / cm 3 Up to 1.3g / cm 3 This offers the advantage that the particles are in better contact with one another and thus the conductivity of the resulting electrode is improved.
[0038] In particular, the silicon-carbon composite mixture has an electrical conductivity ranging from 0.3 S / cm to 2 S / cm, or from 0.5 S / cm to 1.2 S / cm. This provides the following advantages: the resistance of the electrode is reduced, thereby allowing Li ions to react faster with the silicon-carbon composite mixture. Therefore, the charging speed of the lithium ion battery can be increased.
[0039] Preferably, the silicon-carbon composite material has a silicon content in an amount of ≥18 wt.-% to ≤55 wt.-% relative to the silicon-carbon composite material. The silicon content of the total mass of the silicon-carbon composite material is typically between 18 wt.-% and 40 wt.-%, in particular between 26 wt.-% and 36 wt.-%. According to another embodiment, the silicon content of the total mass of the silicon-carbon composite material is typically between 30 wt.-% and 50 wt.-%, in particular between 37 wt.-% and 46 wt.-%. These embodiments can improve the charging process in a very effective manner, in particular with regard to the charging time.
[0040] It may further be preferred that the silicon-carbon composite material has a carbon support, the carbon support has pores, wherein the pores have a diameter of ≥0.5 cm 3 / g total pore volume. Typically, porous carbon has pore space, also referred to as pore volume, wherein the pore space is a group of voids (pores) in the carbon that can be filled with a gas or fluid. This embodiment can significantly reduce the weight of the anode, and therefore significantly reduce the weight of the electrochemical energy storage device.
[0041] This embodiment can be of the utmost importance, especially in the case where the anode and therefore the electrochemical energy storage device is used in mobile applications, such as in vehicles. In addition, the electrochemical properties can also be improved. For this purpose, the porous arrangement offers the advantages of being generally easy to produce, generally having low impurities and a large pore volume. Therefore, porous carbons exhibit good electrical conductivity and high mechanical and chemical stability.
[0042] Preferably, the silicon-carbon composite material is present in a bimodal particle size distribution. Particularly preferably, the first particle size Dv50 is in the range of ≥1 μm to <6 μm, and wherein the second particle size Dv50 is in the range of ≥6 μm to ≤20 μm.
[0043] The particle size distribution can be measured as known in the art. For example, the particle size distribution can be measured by laser scattering of particles in a suspension, or a powder time-of-flight method, or other methods known in the art. As known in the art, the particle size distribution can be expressed as a particle number distribution or a particle volume distribution. Therefore, the particle size distribution can be expressed as Dvx, where D represents the particle diameter, v represents the value corresponding to the volume basis, and x represents the cumulative percentage of the particles. For example, Dv1, Dv10, Dv50, Dv90 and Dv99 are the diameters at which 1%, 10%, 50%, 90% and 99% of the particles in a given volume distribution are located below a specified micron size. The particle size distribution is defined by D0 (the smallest particle in the distribution) and Dv100 (the maximum size of the largest particle); Dv50 is the volume average particle size. The particle size distribution can be described according to one or more modes present in the particle size distribution, wherein the concept of mode is known in the art, such as the maximum value in the distribution. The particle size distribution can be unimodal or multimodal, such as bimodal or trimodal. Patterns within a multimodal particle size distribution may include distinct local maxima within the particle distribution and / or shoulders that can be resolved from the first and / or second derivatives of the particle size distribution.
[0044] The present disclosure provides the following advantages: The bimodal distribution of the composite material enables higher packing density and improved conductivity of the anode electrode.
[0045] In another embodiment, the bimodal silicon-carbon composite material comprises at least one additional carbon and / or at least one additional binder. This results in the following advantages: the carbon increases the conductivity of the electrode and thus provides improved conductivity. At least one additional binder also supports mechanical stability. The additional carbon can be a hard carbon material or graphite carbon or a metal oxide. For example, the compound comprising the oxide is silicon oxide (SiO2). Alternatively, the metal oxide is titanium oxide (TiO2), tin oxide (SnO2) or other metal oxides. The hard carbon material is a non-graphitizable carbon material. Hard carbon provides the following advantages: it remains amorphous at elevated temperatures (typically >1500°C), while "soft" carbon crystallizes and becomes graphite.
[0046] In one embodiment, at least one additional carbon and / or at least one additional binder is dissolved in an aqueous medium.
[0047] In another embodiment, the multimodal silicon-carbon composite is constructed such that the silicon-carbon composite has a 3 Up to 1.5g / cm 3 , especially at 1.1g / cm 3 Up to 1.3g / cm 3 This offers the advantage that the particles are in better contact with one another and thus improves the conductivity of the resulting electrode.
[0048] Alternatively, it may also be advantageous if the silicon-carbon composite material is present in a unimodal particle size distribution. In this regard, it may be particularly preferred that the particle size Dv50 is in the range of ≥7 μm to <12 μm. This embodiment effectively reduces or avoids side reactions because larger particles have a smaller surface area.
[0049] It may be further preferred that the surface area of the silicon-carbon composite material is less than 30 m 2 / g. The surface area is measured according to the BET measurement method, which is a term for an analytical method for determining the size of a surface (especially a porous solid) by gas adsorption. In another embodiment, the BET surface area is measured at 4 m 3 / g to 25m 3 / g.
[0050] This offers the advantage that the resistance of the electrode is reduced, thus allowing the Li ions to react more quickly with the multimodal Si-C composite. Thus, the charging speed of the lithium-ion battery can be further increased.
[0051] The anode may further comprise: carbon black in an amount of ≥ 0.5 wt.-% to ≤ 2 wt.-% relative to the anode. Providing carbon black may even further improve the electrical properties of the anode. As an example, carbon black provides excellent electrical conductivity in the anode, which in turn results in a variety of performance and cost benefits, for example for lithium-ion batteries.
[0052] In a particularly preferred embodiment, the anode may comprise
[0053] - a silicon-carbon composite in an amount of ≥ 65 wt.-% to ≤ 80 wt.-%, relative to the anode, and a silicon content in an amount of ≥ 26 wt.-% to ≤ 32 wt.-%, relative to the silicon carbide composite (10);
[0054] - graphite in an amount of ≥ 9 wt.-% to ≤ 29 wt.-%, such as to 23 wt.-%, relative to the anode;
[0055] - carbon nanotubes in an amount of >0.01 wt.-% to <0.1 wt.-% relative to the anode;
[0056] - carbon black in an amount >0.5 wt.-%, such as >1.5 wt.-% to <3 wt.-%, relative to the anode; and
[0057] - an amount of binder of >2.5 wt.-%, such as >3 wt.-% to <8 wt.-%, relative to the anode.
[0058] In another embodiment, the anode electrode has a density including E greater than 0.01, such as greater than 0.05 or greater than 0.1, wherein E is defined as 1-(tap density of the composite mixture) / (mass average tap density of each fraction), wherein the density is the electrode density measured in an electrode composed of 70wt% composite, 20wt% graphite, and 2wt% Super C65, and 8% PAA.
[0059] The tap density of the particulate silicon-carbon composite material and the silicon-carbon composite material mixture can be measured as known in the art. For example, the tap density can be measured with a PT-TD300 tap density tester, wherein a known mass of powder is loaded into a measuring cylinder, for example until the measuring cylinder is filled to 1 / 2 to 3 / 4 of its total capacity, the measuring cylinder is loaded into the test device, and the loaded measuring cylinder is tapped for a fixed number of taps (e.g., 250 taps) and the new tap volume is recorded, and the tapping process is repeated until the measured volume no longer changes, for example within 2% of the previous reading.
[0060] In another embodiment, an E measurement of an electrode characteristic of a silicon-carbon composite mixture is determined, and individual fractions comprising each mode are measured under otherwise identical conditions.
[0061] Thus, one embodiment provides an anode comprising:
[0062] a) A first silicon-carbon composite material, comprising:
[0063] i. A porous carbon scaffold comprising micropores and mesopores with a total pore volume of not less than 0.5 cm 3 / g;
[0064] ii. a silicon content of 30% to 70% by mass relative to the silicon-carbon composite material;
[0065] iii. a plurality of particles having a Dv50 of 6 μm to 20 μm;
[0066] b) at least one additional silicon-carbon composite material comprising:
[0067] i. at least one additional carbon support comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm 3 / g;
[0068] ii. a silicon content of 30% to 70% by mass relative to the silicon-carbon composite material;
[0069] iii. a plurality of particles having a Dv50 of 1 μm to 6 μm; and
[0070] c) 10% to 90% by mass of the first silicon-carbon composite material and 10% to 90% by mass of at least one additional silicon-carbon composite material relative to the silicon-carbon composite material.
[0071] A further embodiment provides an anode comprising:
[0072] a) A first silicon-carbon composite material, comprising:
[0073] i. A porous carbon scaffold comprising micropores and mesopores with a total pore volume of not less than 0.5 cm 3 / g;
[0074] ii. a silicon content of 30% to 70% by mass relative to the silicon-carbon composite material;
[0075] iii. a plurality of particles having a Dv50 of 6 μm to 20 μm;
[0076] b) at least one additional silicon-carbon composite material comprising:
[0077] i. at least one additional carbon support comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm 3 / g;
[0078] ii. a silicon content of 30% to 70% by mass relative to the silicon-carbon composite material;
[0079] iii. a plurality of particles having a Dv50 of 1 μm to 6 μm;
[0080] c) 10% to 90% by mass of the first silicon-carbon composite material and 10% to 90% by mass of at least one additional silicon-carbon composite material;
[0081] d) Less than 30m 2 Surface area / g;
[0082] e) E is greater than 0.01, wherein E is defined as 1-(tap density of the composite mixture) / (mass average tap density of the individual fractions); and
[0083] f) The E measured value of the tap density of the silicon-carbon composite mixture was determined and the individual fractions comprising each mode were measured under otherwise identical conditions.
[0084] Another embodiment provides an anode comprising:
[0085] a) A first silicon-carbon composite material, comprising:
[0086] i. A porous carbon scaffold comprising micropores and mesopores with a total pore volume of not less than 0.5 cm 3 / g;
[0087] ii. a silicon content of 30% to 70% by mass relative to the silicon-carbon composite material;
[0088] iii. a plurality of particles having a Dv50 of 6 μm to 20 μm;
[0089] b) at least one additional silicon-carbon composite material comprising:
[0090] i. at least one additional carbon support comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm 3 / g;
[0091] ii. a silicon content of 30% to 70% by mass relative to the silicon-carbon composite material;
[0092] iii. a plurality of particles having a Dv50 of 1 μm to 6 μm;
[0093] c) 10% to 90% by mass of the first silicon-carbon composite material and 10% to 90% by mass of at least one additional silicon-carbon composite material;
[0094] d) Less than 30m 2 / g surface area; and
[0095] e) E is greater than 0.01, where E is defined as 1-(conductivity of the composite material) / (mass average conductivity of each fraction).
[0096] Regarding the preparation of silicon-carbon composite materials, one embodiment provides a method for preparing a silicon-carbon composite mixture, comprising the following steps:
[0097] a) providing a porous carbon support;
[0098] b) comminuting the porous carbon scaffold to produce at least two particulate fractions, comprising:
[0099] i. a first porous carbon composite material comprising a plurality of particles having a Dv50 of 6 μm to 20 μm;
[0100] ii. at least one additional porous carbon composite material comprising a particle size distribution having a Dv50 of from 1 μm to 6 μm;
[0101] c) impregnating silicon into the pores of at least two particle fractions of the porous carbon composite material by chemical vapor infiltration; and
[0102] d) blending the first particulate silicon-carbon composite with at least one additional particulate silicon-carbon composite.
[0103] Another embodiment provides a method for preparing a silicon-carbon composite mixture, comprising the steps of:
[0104] a) Providing a porous carbon scaffold
[0105] b) comminuting the porous carbon scaffold to produce at least two particulate fractions, comprising:
[0106] i. a first porous carbon composite material comprising a plurality of particles having a Dv50 of 6 μm to 20 μm;
[0107] ii. at least one additional porous carbon composite material comprising a particle size distribution having a Dv50 of from 1 μm to 6 μm;
[0108] c) impregnating silicon into the pores of at least two particle fractions of the porous carbon composite material by chemical vapor infiltration; and
[0109] d) applying a coating onto the surfaces of at least two particle fractions of the porous silicon-carbon composite material by chemical vapor deposition; and
[0110] e) blending the first particulate silicon-carbon composite with at least one additional particulate silicon-carbon composite.
[0111] Thus, generally, silicon-carbon composites can be prepared by infiltrating a porous carbon material with silicon, such as with SiH4 and / or other gases such as trimethylaluminum.
[0112] One specific embodiment provides a method of making an anode electrode comprising the silicon-carbon composite mixture described herein, comprising the steps of:
[0113] a) mixing the silicon-carbon composite material mixture with at least one carbon such as graphite, and carbon nanotubes to produce a mixture,
[0114] b) combining the mixture with a binder solution in a twin-screw extruder to form an electrode paste,
[0115] c) applying the electrode paste to the conductor, thereby producing at least one electrode,
[0116] d) drying at least one electrode at a temperature of 100°C to 140°C.
[0117] Next, in the first step, a porous carbon scaffold material is produced. In a preferred embodiment, the carbon scaffold is prepared according to U.S. Publication No. 2017 / 0015559. In a preferred embodiment, the porous carbon scaffold carbon is an amorphous carbon containing nitrogen. The use of nitrogen (N) improves the conductivity of the amorphous carbon.
[0118] In a preferred embodiment, the porous carbon support includes micropores, mesopores, and / or macropores, wherein micropores are defined as pores having a diameter less than 2 nm, mesopores are defined as pores having a diameter of 2 nm to 50 nm, and mesopores are defined as pores having a diameter greater than 50 nm. As used herein, the percentages "microporosity," "mesoporosis," and "macroporosis" refer to the percentage of micropores, mesopores, and macropores, respectively, as a percentage of the total pore volume. For example, a carbon support having a microporosity of 90% is a carbon support in which 90% of the total pore volume of the carbon support is microporous.
[0119] In a further step, the polymer gel may be pyrolyzed at a temperature of 700° C. to 950° C. in nitrogen to obtain the silicon-carbon composite material.
[0120] In a further step, the silicon-carbon composite material is comminuted by grinding to produce at least two silicon-carbon composite materials having at least two fractions, specifically, one of the at least two silicon-carbon composite materials has a particle size distribution in which the percentage Dv50=6 μm to 20 μm and the other fraction has a particle size distribution in which the percentage Dv50=1 μm to 6 μm. This comminution can be accomplished as known in the art, for example, using a hammer mill, ball mill, jet mill or other abrasive mill abrasive grinding methods to reduce the particle size.
[0121] The two or more fractions of the silicon-carbon composite material each comprise a porous carbon scaffold having certain properties (e.g., properties disclosed in U.S. Publication No. 2017 / 0170477).
[0122] With regard to further advantages and technical features of the anode, they relate to the electrochemical energy storage device, to the vehicle and to the exemplary embodiments and figures.
[0123] Further described is an electrochemical energy storage device comprising:
[0124] - an anode as described above;
[0125] -cathode;
[0126] - a separator disposed between the cathode and the anode; and
[0127] - An electrolyte comprising lithium ions.
[0128] The general arrangement of an electrochemical energy storage device may be chosen as generally known in the art. However, an important feature of such a device is that it comprises an anode as described in more detail above.
[0129] In addition to the anode, the electrochemical energy storage device or the electrochemical cell of the electrochemical energy storage device comprises a cathode. The cathode can generally be formed as known in the art of lithium batteries.
[0130] Typically, the cathode may include a1+x TM 1-x A single crystal (SC), polycrystalline (PC) or a mixture of single crystal (SC) and polycrystalline (PC) forms of a layered transition metal oxide material of O2, wherein TM is Ni, Co, Mn, Al, Zr, Ti, Nb, W. The amounts of these metals are preferably as follows: Ni = 0.7 to 0.95, Co = 0.01 to 0.15, Mn = 0.01 to 0.1, Al = 0 to 0.03, Zr = 0 to 0.01, Nb, Ti, W = 0 to 0.02, wherein x can be any value between 0 and 0.05. In addition, in the case where there is a mixture of single crystal (SC) and polycrystalline (PC) forms, the mixture ratio can be 20 to 35 wt% SC and 65 to 80% PC.
[0131] In particular, the cathode comprises lithium nickel manganese cobalt oxide, wherein the lithium nickel manganese cobalt oxide is present in a mixture of polycrystalline form and single crystal form. According to this embodiment, the electrochemical characteristics of the electrochemical energy storage device can be improved even further, in particular with regard to the cycling behavior and in particular with regard to the charging time.
[0132] Regarding the separator, the separator can also be generally formed as known in the prior art. Preferably, the separator can include three layers of polymer. Such a polymer can, for example, include an inorganic coating, such as Al2O3, BaTiO3.
[0133] It may further be preferred that the separator is laminated to the anode. This allows the advantages of improving the stacking of electrodes, since the separator is already fixed to the anode electrode.
[0134] The electrolyte may include at least one compound selected from the group consisting of fluoroethylene carbonate, propylene carbonate, ethylene carbonate, lithium hexafluorophosphate, and lithium bis(fluorosulfonyl)imide. It can be shown that when used in a lithium battery, such electrolytes exhibit excellent properties. Typically, the electrolyte may include a mixture of LiPF6 and LiFSi, wherein the electrolyte may be based on fluoroethylene carbonate (FEC)-based substances. It may exemplarily include 1 to 10 wt.-% of FEC, 0 to 20 wt.-% of ethylene carbonate (EC), 0 to 30 wt.-% of propylene carbonate (PC), and optional additional additives, each relative to the electrolyte.
[0135] The electrochemical energy storage device as described above comprising the anode exhibits the advantage of excellent charging time, which allows the electrochemical energy storage device to be charged from a very low state of charge to a very high state of charge in a very short time. This significantly improves market acceptance.
[0136] In particular, considering secondary batteries used in vehicles, charging time is an important factor that can improve the acceptance of electric vehicles.
[0137] In addition to the above and the charging time, other characteristics of the anode are not deteriorated, such as long life, high cycle stability and damage resistance.
[0138] As regards further advantages and technical features of the electrochemical energy storage device, they relate to the anode, to the vehicle and to the exemplary embodiments and the figures.
[0139] An electric vehicle is further described, comprising an electric engine and an electrochemical energy storage device for supplying electrical energy to the electric engine, characterized in that the electrochemical energy storage device is formed as described above.
[0140] The vehicle may generally be any vehicle that is electrically driven. In particular, the electric vehicle may be a fully electric vehicle or a so-called hybrid vehicle. However, it may be preferred that the electric vehicle is a fully electric land vehicle, such as a car, bus or truck.
[0141] The vehicle includes an electric motor and an electrochemical energy storage device for supplying electrical energy to the electric motor.
[0142] The electric motor can generally be arranged as known in the art, for example, the electrically driven motor can be a permanent synchronous machine as an electric motor or an asynchronous machine as an electric motor. Of course, both motors can be present and can be supplied with electrical energy from an electrochemical energy storage device. The latter is designed as defined above.
[0143] The anodes and therefore the corresponding electrochemical energy storage devices exhibit the advantage of excellent charging times, which allow the electrochemical energy storage device to be charged from a very low state of charge to a very high state of charge in a very short time. This significantly improves market acceptance.
[0144] In particular, considering secondary batteries used in vehicles, charging time is an important factor that can improve the acceptance of electric vehicles. Therefore, improving charging time in particular is an important characteristic of secondary batteries for vehicles. However, it should of course also be pointed out that the anodes described here and therefore the electrochemical energy storage devices are not limited to use in vehicles.
[0145] In addition to the above and the charging time, other characteristics of the anode are not deteriorated, such as long life, high cycle stability and damage resistance.
[0146] As regards further advantages and technical features of the vehicle, they relate to the anode, to the electrochemical energy storage device and to the exemplary embodiments and figures.
[0147] In general, single or multiple features and in particular the amounts of the corresponding compounds can be transferred between the individual embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0148] In the following, the invention is explained by way of example with reference to the accompanying drawings and by the accompanying examples of preferred embodiments, wherein the features indicated below may each constitute aspects of the invention individually or in combination:
[0149] Figure 1 An exemplary electrochemical storage device having a fabricated anode comprising a silicon-carbon composite material is shown;
[0150] Figure 2 An exemplary electrochemical storage device according to another embodiment having an anode including a silicon-carbon composite material is shown;
[0151] Figure 3 The capacity and coulombic efficiency of the electrochemical energy storage device according to the present invention over multiple charging cycles are shown;
[0152] Figure 4 The temperature occurring in the electrochemical energy storage device according to the present invention and the charge capacity for different charging parameters are shown;
[0153] Figure 5 shows the temperature distribution of the electrochemical energy storage device according to the present invention obtained at a C-rate of 3C;
[0154] Figure 6 shows the temperature distribution of an electrochemical energy storage device according to the present invention obtained at a C-rate of 4C; and
[0155] Figure 7 The temperature distribution of the electrochemical energy storage device according to the invention obtained at a C-rate of 5C is shown. DETAILED DESCRIPTION
[0156] In the drawings, the same reference numerals indicate similar elements. The sizes and relative positions of the elements in the drawings are not necessarily drawn to scale, and some of these elements are enlarged and positioned to improve the legibility of the drawings. Further, the specific shapes of the drawn elements are not intended to convey any information about the actual shape of the specific elements, and are selected only for ease of identification in the drawings.
[0157] Figure 1 A cross-sectional view of an exemplary electrochemical storage device 100 having an anode 110 (also referred to as an anode electrode) including the silicon-carbon composite material 10 is shown.
[0158] The electrochemical storage device 100 is formed as a lithium-ion battery cell. The electrochemical storage device 100 includes at least one anode 110, at least one cathode 120, and a separator 130 disposed between the cathode 120 and the anode 110. The cathode 120 preferably includes a transition metal oxide.
[0159] In addition, an electrolyte 140 containing lithium ions is provided in a cell housing 150 of the electrochemical storage device 100. The electrochemical storage device 100 may be formed as a lithium ion battery cell in a bag form. Therefore, the cell housing 150 may be formed as an aluminum bag. The anode 110, the cathode 120, and the separator 130 are also arranged in the cell housing 150.
[0160] It should be noted that Figure 1 A simplified cross-sectional view is shown. The anode 110, cathode 120 and separator 130 are typically formed in multiple layers that are wound or folded to optimize packaging and to increase the possible surface area of the electrolyte 140. In the illustrated embodiment, only one layer of the components is visible for illustration purposes.
[0161] The anode 110 is coated on both sides with the silicon-carbon composite material 10. The surface coating 11 of the silicon-carbon composite material 10 is achieved on the surface area of the silicon-carbon composite material 10 that is not in contact with the current collector 111 of the anode 110.
[0162] By utilizing an anode 110 having a silicon-carbon material 10, electrical performance is significantly improved, especially in terms of charging time.
[0163] exist Figure 2 Another exemplary electrochemical storage device 100 is shown in FIG. The electrochemical storage device 100 includes an anode 110 having a silicon-carbon composite material 10. Figure 1 Compared to the embodiment shown in , the surface coating 11 of the silicon-carbon composite material 10 is partially applied to the surface area of the silicon-carbon composite material 10 , so that a partial surface area of the silicon-carbon composite material 10 remains without the surface coating 11 .
[0164] In the following, an exemplary electrochemical energy storage device 100 is provided and the cycling behavior is examined.
[0165] Electrochemical energy storage device 100 is arranged as follows.
[0166] The anode 110 is formed from the following components (defined in wt.-% relative to the anode):
[0167] -73% Si carbon composite material (Group 14);
[0168] - 20% graphite (Imerys, KS6);
[0169] -1.95% carbon black (Imerys, Super C65;
[0170] - 0.05% CNT (Tuball, 0.2 to 0.4% SW-CNT in CMC-based aqueous solution);
[0171] -5% CMC / SBR in water (BASF SE)
[0172] The cathode 120 is formed from the following components (defined in wt.-% relative to the anode):
[0173] - 96% cathode material as a mixture of 70% NCM-83-12-05 and polycrystalline 30% NCM-83-12-05 and single crystal;
[0174] -2% Super C65 (carbon black);
[0175] - 2% polyvinylidene fluoride (PVDF) in N-methyl-2-pyrrolidone (NMP)
[0176] The separator 130 used includes a three-layer polymer separator having a thickness of about 12 μm and an inorganic coating such as Al2O3 on both sides of the separator 130 to improve the safety of the battery. The electrolyte 140 includes a mixture of 1 mole of Li salt (60% LiPF6 and 40% LiFSi) in a solvent mixture of 5% FEC, 5% PC, 20% EC and 68% EMC, 2% VC.
[0177] Figure 3 The electrochemical behavior of an electrochemical energy storage device 100 arranged as described above is shown. In particular, the behavior over a number of charging cycles at different C-rates, ie over 250 cycles, is shown.
[0178] It has been shown that at elevated temperatures or 45°C and with rapid charging the capacity decreases only in an acceptable manner over a long life (i.e. over 250 charging cycles). In addition, the coulombic efficiency (which describes the charging efficiency of the electron transfer in the battery) remains in a very good range. Therefore, Figure 1 It is shown that the electrochemical energy storage device 100 according to the present invention maintains its good electrical performance even over a large number of charging cycles.
[0179] Figure 4 The temperatures occurring in the battery cells and the charge capacities for different charging parameters are shown. In detail, Figure 4The charging and discharging behavior at different charging and discharging rates or in other words at different so-called C-rates is shown. In this regard, a C-rate of 1C / 1C describes a complete charging / discharging of the battery cell in each case within 1 hour. Accordingly, a C-rate of 3C / 1C describes a complete charging of the battery cell in 20 minutes and a complete discharging of the battery cell in 1 hour, a C-rate of 4C describes a complete charging of the battery cell in 15 minutes and a complete discharging of the battery cell in 1 hour, and a C-rate of 5C describes a complete charging of the battery cell in 12 minutes and a complete discharging of the battery cell in 1 hour.
[0180] Before the fast charging experiments, the battery cells were transferred to the same starting conditions of 5% SOC with a constant current and a C-rate of 0.1C. After that, fast charging with 3C, 4C and 5C rates was started at 5% state of charge (SOC) and approximately until 80% SOC was reached. For this, when the corresponding parameter of 4.2V as a threshold was reached, it was first charged with a constant current (CC) and then with a constant voltage (CV). This CC-CV charging method is a known hybrid method combining the two aforementioned charging methods. It uses CC charging in the first charging stage, and when the voltage reaches the maximum safety threshold, the charging process switches to the CV charging method.
[0181] Figure 4 It is shown that when charging is started from a comparable starting temperature, the end temperature is clearly maintained at a very well acceptable value even when using the fastest C-rate (5C). Thus, it is shown that the electrochemical energy storage device 100 can perform charging cycles without providing any temperature problems, which is an important factor for using such an electrochemical energy storage device 100, for example, in a vehicle.
[0182] In the following Table 1, the corresponding charging times are given.
[0183] Table 1: Charging time at different C-rates
[0184]
[0185]
[0186] According to Table 1, it can be shown that excellent charging times can be achieved. The most important value for electric vehicles is in particular the CC charging sequence, since charging from 5 to 80% SOC is the preferred charging scheme. When a C-rate of 5C is used, the charging time from 5 to 80% SOC lasts only less than 7 minutes, which is difficult to achieve when using secondary batteries according to the prior art. In addition, excellent charging times can be achieved even when using smaller C-rates.
[0187] Figures 5 to 7Further shown is the temperature distribution over a number of hours and thus over a number of charging cycles with different C-rates. Figure 5 shows the temperature distribution of the electrochemical energy storage device 100 obtained by charging / discharging at a C-rate of 3C / 1C, Figure 6 shows the temperature distribution of the electrochemical energy storage device obtained by charging / discharging at a C-rate of 4C / 1C, and Figure 7 The temperature distribution of the electrochemical energy storage device obtained by charging / discharging at a C-rate of 5C / 1C is shown.
[0188] With a C-ratio of 3C / 1C, the average temperature was at 48.22° C. and the maximum temperature was at 51.4° C. In addition, with a C-ratio of 4C / 1C, the average temperature was at 48.48° C. and the maximum temperature was at 52.8° C., and with a C-ratio of 5C / 1C, the average temperature was at 48.65° C. and the maximum temperature was at 54.5° C.
[0189] It can be shown that the temperature is kept within a well-managed range. Therefore, the occurrence of temperature-related problems can be reduced and safe operation can be ensured. Moreover, the increase in temperature is very limited even with increasing C-rate.
Claims
1. An anode (110) for an electrochemical energy storage device (100), comprising at least: - a silicon-carbon composite material (10) in an amount of ≥ 45 wt.-% to ≤ 90 wt.-%, relative to the anode (110), - graphite in an amount of ≥ 5 wt.-% to ≤ 47 wt.-%, relative to the anode (110); - carbon nanotubes in an amount of >0 wt.-% to <1 wt.-% relative to the anode (110); and - a binder, in particular a polymeric binder, in particular in an amount of 2.5 to 8 wt.-%, relative to the anode (110).
2. The anode (110) according to claim 1, characterized in that The silicon-carbon composite material (10) has a silicon content in an amount of ≥18 wt.-% to ≤55 wt.-%, relative to the silicon-carbon composite material (10).
3. The anode (110) according to claim 1 or 2, characterized in that: The silicon-carbon composite material (10) comprises a carbon support, wherein the carbon support has pores, wherein the pores of the carbon support have a diameter of ≥0.5 cm 3 / g total pore volume.
4. The anode (110) according to any one of claims 1 to 3, characterized in that: The silicon-carbon composite material (10) is present in a bimodal particle size distribution, wherein a first particle size d50 is in the range of ≥1 μm to <6 μm, and wherein a second particle size d50 is in the range of ≥6 μm to ≤20 μm.
5. The anode (110) according to any one of claims 1 to 3, characterized in that: The silicon-carbon composite material (10) is present in a monomodal particle size distribution, wherein the particle size d50 is in the range of ≥7 μm to <12 μm.
6. The anode (110) according to any one of claims 1 to 5, characterized in that The surface area of the silicon-carbon composite material (10) is less than 30 m 2 / g.
7. The anode (110) according to any one of claims 1 to 6, characterized in that The carbon nanotubes are single-walled carbon nanotubes.
8. The anode according to any one of claims 1 to 7, characterized in that The binder is a styrene-butadiene rubber / carboxymethyl cellulose (CMC / SBR) mixture, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA).
9. The anode (110) according to any one of claims 1 to 8, characterized in that The anode (110) further comprises carbon black, wherein the amount of the carbon black is ≥ 0.5 wt.-% to ≤ 2 wt.-%, relative to the anode (110).
10. The anode (110) according to any one of claims 1 to 9, characterized in that: The anode (110) comprises: - a silicon-carbon composite material (10) in an amount of ≥65 wt.-% to ≤80 wt.-% relative to the anode (110); and a silicon content in an amount of ≥26 wt.-% to ≤32 wt.-% relative to the silicon carbide composite material (10); - graphite in an amount of ≥ 9 wt.-% to ≤ 29 wt.-%, relative to the anode (110); - carbon nanotubes in an amount of >0.01 wt.-% to <0.1 wt.-% relative to the anode (110); - carbon black in an amount of >0.5 wt.-% to <3 wt.-%, relative to the anode (110); as well as - a binder in an amount of >2.5 wt.-% to <8 wt.-%, relative to the anode (110).
11. An electrochemical energy storage device (100), comprising: - an anode (110) according to any one of claims 1 to 10; - cathode (120); - a separator (130) disposed between the cathode (120) and the anode (110); and - An electrolyte (140) containing lithium ions.
12. The electrochemical energy storage device (100) according to claim 11, characterized in that: The cathode (120) comprises lithium nickel manganese cobalt oxide, wherein the lithium nickel manganese cobalt oxide exists in a mixture of polycrystalline and single crystalline forms.
13. The electrochemical energy storage device (100) according to claim 11 or 12, characterized in that: The separator (130) is laminated to the anode (110).
14. The electrochemical energy storage device (100) according to any one of claims 11 to 13, characterized in that: The electrolyte (140) includes at least one compound selected from the group consisting of fluoroethylene carbonate, propylene carbonate, ethylene carbonate, lithium hexafluorophosphate, and lithium bis(fluorosulfonyl)imide.
15. An electric vehicle comprising an electric engine and an electrochemical energy storage device (100), wherein the electrochemical energy storage device is used to supply electric energy to the electric engine, characterized in that: The electrochemical energy storage device (100) is formed according to any one of claims 11 to 14.
Citation Information
Patent Citations
Novel methods for sol-gel polymerization in absence of solvent and creation of tunable carbon structure from same
US20170015559A1
Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof
US20170170477A1